2009
DOI: 10.1159/000252772
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Addenbrooke’s Cognitive Examination (ACE) in a Persian-Speaking Population

Abstract: Use of reliable screening and diagnostic tests for assessment of cognitive abilities in neurological patients is rapidly increasing in clinical practice. This is due to the increase in the prevalence of dementias and the raised awareness of cognitive impairment in neurological disorders. Two well-known bedside screening tests for dementias among the English-speaking population are the Mini Mental State Examination (MMSE) and Addenbrooke’s Cognitive Examination (ACE). However, such tests have not been developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Sensitivity and specificity of Persian format of this test was 91% and 93%, respectively, with the cutoff of 78. [ 19 ]…”
Section: Methodsmentioning
confidence: 99%
“…Sensitivity and specificity of Persian format of this test was 91% and 93%, respectively, with the cutoff of 78. [ 19 ]…”
Section: Methodsmentioning
confidence: 99%
“…A score between 78 and 85 showed mild cognitive impairment, and less than 78 was indicative of AD. The calculated Cronbach's alpha in this study was 0.84 overall (24).…”
Section: Methodsmentioning
confidence: 49%
“…Additionally, the cognitive profile differed significantly amongst the psychiatric and dementia subgroups, suggesting that the NUCOG may offer clinicians additional utility in the diagnostic process. Besides the MMSE, the only other cognitive assessment tool available in Persian is the ACE, which has recently also been validated in a Persian-speaking population although this study used a smaller sample size (n = 135) and only included controls, individuals diagnosed with MCI and patients with SDAT, with the aim of distinguishing these three groups from each other [15] . This study showed that the ACE strongly differentiated MCI and SDAT from the healthy control group, and that the ACE significantly outperformed the MMSE with regard to sensitivity and specificity in discriminating SDAT and MCI from healthy individuals.…”
Section: Discussionmentioning
confidence: 99%